Characteristics of emergency medicine residency programs in Colombia (2017)
Introduction: Emergency medicine (EM) is in different stages of development around the world. Colombia has made significant strides in EM development in the last two decades and recognized it as a medical specialty in 2005. The country now has seven EM residency programs: three in the capital city of Bogotá, two in Medellin, one in Manizales, and one in Cali. The seven residency programs are in different stages of maturity, with the oldest founded 20 years ago and two founded in the last two years. The objective of this study was to characterize these seven residency programs. Methods: We conducted semi-structured interviews with faculty and residents from all the existing programs in 2013-2016. Topics included program characteristics and curricula. Results: Colombian EM residencies are three-year programs, with the exception of one four-year program. Programs accept 3-10 applicants yearly Only one program has free tuition and the rest charge tuition. The number of EM faculty ranges from 2-15. EM rotation requirements range from 11-33% of total clinical time. One program does not have a pediatric rotation. The other programs require 1-2 months of pediatrics or pediatric EM. Critical care requirements range from 4-7 months. Other common rotations include anesthesia, general surgery, internal medicine, obstetrics, gynecology, orthopedics, ophthalmology, radiology, toxicology, psychiatry, neurology, cardiology, pulmonology, and trauma. All programs offer 4-6 hours of protected didactic time each week. Some programs require Advanced Cardiac Life Support, Pediatric Advanced Life Support and Advanced Trauma Life Support, with some programs providing these trainings in-house or subsidizing the cost. Most programs require one research project for graduation. Resident evaluations consist of written tests and oral exams several times per year. Point-of-care ultrasound training is provided in four of the seven programs. Conclusion: As emergency medicine continues to develop in Colombia, more residency programs are expected to emerge. Faculty development and sustainability of academic pursuits will be critically important. In the long term, the specialty will need to move toward certifying board exams and professional development through a national EM organization to promote standardization across programs. © 2017 Patiño et al.